Synthesis, characterization and biochemical study of novel ester prodrugs containing aspirin and ibuprofen - Sh. Abdul Razzak, Firas; S. Hameed, Ayad; M. Aziz, Noori (Tikrit Journal of Pharmaceutical Sciences, 2023)
Aspirin and ibuprofen are aryl acids of nonsteroidal anti inflammatory drugs with goodanalgesic. For reducing the gastrointestinal toxicity associated with presence free carboxylicacid functional group in aspirin and ibuprofen, therefore the present work is aimed tosynthesize a novel ester prodrugs of these two drugs. These two novel prodrugs were preparedby the reaction of aspirin or ibuprofen acid chloride with 1,2:5,6-di-O-isopropylidene-α-Dglucofuranose,then deprotection of ester prodrug of aspirin was also accomplished using 70%acetic acid. The purity of the synthesized compounds was established by (TLC), columnchromatography, while their structures were confirmed by (FT-IR, 1HNMR, 13CNMR). Then36 rabbits has been obtained and divided to six groups to show the bioavailability of theprepared prodrugs at some biochemical parameters and compared with the parent drugs andcontrol group. Statistical analysis revealed significant increases in the levels of creatinekinase, alkaline phosphatase, aspartate aminotransferase, alanine amino transferase,glutathione, malondialdehyde, creatinine, uric acid, concentration of Cu, and significantdecreases in the levels of choline esteras, total protein, Zn concentration, while the resultsshowed no significant increases in the activity of lactate dehydrogenase, acid phosphataseand no significant decreases in the levels of albumin, globulin, and iron concentration for theprepared prodrugs compared with the control group. Finally, to ensure the release of parentdrugs(aspirin or ibuprofen), hydrolytic studies of the ester prodrugs were obtained at differentpH (2, 4, 10 and 12) at 25οC, the results showed that the hydrolysis at basic pH were fasterthan acidic pH, so it means that the most hydrolysis will obtain at intestine not at stomach.